Lulu & Rocky in Indianapolis - Joosse, Barbara M.; Graef, Renee (Sleeping Bear Press, 2020)
"Fox kits Lulu and her cousin Rocky visit Indianapolis, exploring sights like the Dinosphere at the Children's Museum, Central Canal, Indianapolis Motor Speedway, as well as unexpected gems"--
Ages 4-8
Keywords: Indianapolis (Ind.) -- Description and travel -- Juvenile literature